WOOD PROPERTIES OF POPULUS DELTOIDES 77.51 GROWN IN GILAN, IRAN - Abbas Fakhryan roghani (Regional Information Center for Science and Technology (RICeST), 2001)
Threes, six and 12 years old sample trees of Populos deltoides 77.51 were randomly selected and felled at the safrabasteh research station located in Gilan province. Sample tree transferred to the Alborz research center- Karaj for Laboratory studies; The Laboratory studies included determination of physical, anatomical and chemical composition of revealed that with increasing trees age, fiber length and fiber diameter increased. There was significant differences among three ages studied at I percent probability.